very rare localization for metastasis of breast carcinoma in the urinary bladder wall - Inic, Zorka; Milovic-Kovacevic, Marijana; Zivkovic, Ognjen; Zegarac, Milan; Buta, Marko; Petrovic, Ognjen; Markovic, Ivan (Medical Research, 2025)
Introduction: As a widespread malignancy in women throughout the world, breast cancer has an extremely high incidence and mortality rate and therefore poses a serious public health concern. Metastasis of breast carcinoma in the urinary bladder wall poses a challenge in diagnosis because it is a rare and sometimes asymptomatic disease. This paper aims to present a rare case of urinary bladder metastasis originating from invasive lobular breast carcinoma and to emphasize the importance of recognizing atypical metastatic sites. Case Report: A 58-year-old woman with a three-year history of lobular carcinoma of the right breast presented with urinary symptoms and bilateral hydronephrosis. The initial tumor was triple-negative, staged T4bN3M0. Following neoadjuvant chemotherapy (anthracyclines and taxanes), radiotherapy, and modified radical mastectomy. The histopathological assessment of tumor response to therapy: almost complete response (pNCR), and two of ten lymph nodes were positive for metastases. The treatment was continued with Capecitabine in an adjuvant approach (8 cycles), and the patient remained asymptomatic for two years. Subsequently, she developed urosepsis and was hospitalized for bilateral hydronephrosis and renal calculi. Imaging (CT) revealed retroperitoneal lymphadenopathy, and cystoscopy showed bullous edema of the bladder wall. The histopathological examination after TUR showed infiltratory carcinoma of the urinary bladder wall, and immunohistochemical staining was positive for GATA3, GCDFP-15, CDX2, and Mamaglobin. It was concluded that it was a metastasis of breast carcinoma in the urinary bladder wall. Conclusion: Despite therapeutic advances, prognosis remains poor. Awareness of this unusual metastatic pattern is crucial for timely recognition, accurate diagnosis, and multidisciplinary management.